Extensive Karyotype Reorganization in the Fish Gymnotus arapaima (Gymnotiformes, Gymnotidae) Highlighted by Zoo-FISH Analysis - Machado, Milla de Andrade; Pieczarka, Julio C.; Silva, Fernando H. R.; O'Brien, Patricia C. M.; Ferguson-Smith, Malcolm A.; Nagamachi, Cleusa Y. (Frontiers in Genetics, 2018)
The genus Gymnotus (Gymnotiformes) contains over 40 species of freshwater electric fishes exhibiting a wide distribution throughout Central and South America, and being particularly prevalent in the Amazon basin. Cytogenetics has been an important tool in the cytotaxonomy and elucidation of evolutionary processes in this genus, including the unraveling the variety of diploid chromosome number (2n = from 34 to 54), the high karyotype diversity among species with a shared diploid number, different sex chromosome systems, and variation in the distribution of several Repetitive DNAs and colocation and association between those sequences. Recently whole chromosome painting (WCP) has been used for tracking the chromosomal evolution of the genus, showing highly reorganized karyotypes and the conserved synteny of the NOR bearing par within the clade G. carapo. In this study, painting probes derived from the chromosomes of G. carapo (GCA, 2n=42, 30 m/sm + 12 st/a) were hybridized to the mitotic metaphases of G. arapaima (GAR, 2n=44, 24 m/sm + 20 st/a). Our results uncovered chromosomal rearrangements and a high number of repetitive DNA regions. From the 12 chromosome pairs of G. carapo that can be individually differentiated (GCA1–3, 6, 7, 9, 14, 16 and 18–21), six pairs (GCA 1, 9, 14, 18, 20, 21) show conserved homeology with GAR, five pairs (GCA 1, 9, 14, 20, 21) are also shared with cryptic species G. carapo 2n=40 (34 m/sm + 6 st/a) and only the NOR bearing pair (GCA 20) is shared with G. capanema (GCP 2n=34, 20 m/sm + 14 st/a). The remaining chromosomes are reorganized in the karyotype of GAR. Despite the close phylogenetic relationships of these species, our chromosome painting studies demonstrate an extensive reorganization of their karyotypes.